Implementation of Spiritual Leadership Model in Improving Teacher Quality (Case Study at Pondok Pesantren Modern Al Kamil Cianjur) - Rizqi Ali Azhar; Asep Suryana; Abubakar (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to obtain information about how to implement and influence the spiritual leadership model of the school principal in improving the quality of teachers in Islamic boarding schools. This study took data using a qualitative approach with descriptive methods. The sampling technique uses Purfocefull technique as the data collection technique. This research was conducted at the Al Kamil Modern Islamic Boarding School, Cianjur, West Java. The results of this study obtained information about how the principal at Modern Islamic Boarding School Al Kamil Cianjur implements his spiritual leadership model in schools to improve teacher quality. The implication of this research is that if this spiritual leadership model is implemented in schools it can improve the quality of leadership which has implications for improving the quality of teachers and achieving the goals that have been planned before.